International trade and the role of market transparency - Udo Broll; Bernhard Eckwert; Kit Pong Wong (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2010)
The paper examines the economic role of market transparency on the decision problems of an international firm. Transparency is described in terms of the informativeness of a publicly observable signal. With higher transparency, the signal conveys more precise information about the random foreign exchange rate. We analyze the interaction between market transparency, ex ante expected production, domestic sales, and exports of the firm. Furthermore, we discuss the welfare implications of more transparency in the foreign exchange market for the firm and domestic consumers.
Keywords: F11; F23; G14; G15; 330; Blackwell theorem; information system; transparency; hedging; international trade